Application of Convergent Science and Technology toward Ocular Disease Treatment - Ayça Bal-Öztürk; Ece Özcan-Bülbül; Hazal Ezgi Gültekin; Berivan Cecen; Ebru Demir; Atefeh Zarepour; Sibel Cetinel; Ali Zarrabi (Pharmaceuticals, 2023)
Eyes are one of the main critical organs of the body that provide our brain with the most information about the surrounding environment. Disturbance in the activity of this informational organ, resulting from different ocular diseases, could affect the quality of life, so finding appropriate methods for treating ocular disease has attracted lots of attention. This is especially due to the ineffectiveness of the conventional therapeutic method to deliver drugs into the interior parts of the eye, and the also presence of barriers such as tear film, blood-ocular, and blood-retina barriers. Recently, some novel techniques, such as different types of contact lenses, micro and nanoneedles and in situ gels, have been introduced which can overcome the previously mentioned barriers. These novel techniques could enhance the bioavailability of therapeutic components inside the eyes, deliver them to the posterior side of the eyes, release them in a controlled manner, and reduce the side effects of previous methods (such as eye drops). Accordingly, this review paper aims to summarize some of the evidence on the effectiveness of these new techniques for treating ocular disease, their preclinical and clinical progression, current limitations, and future perspectives.